IMPLIKASI HADIS AT-TIRMIDHĪ NOMOR 3638 DALAM IJAZAH KHAT TERHADAP KEINDAHAN DAKWAH QALAM KHATHTHATH - Vira Dindia Arianti; Muhid Muhid; Andris Nurita (IAIN Syekh Nurjati Cirebon, 2023)
The science of khat is a science that introduces the forms of single letters, theirarrangement and ways of assembling them into composed writing. But in the era ofthe current generation, many don't care about the scientific aspects of khat, manypeople prefer to learn easily and quickly by using digital calligraphy applications.Whereas khat science has a clear sanad and identity. Of course the khat learningprocess is very accurate, because it presents theories on how to write the correctArabic letters and khat students in the final process of completing their learning willend with writing a diploma. That the diploma that has been compiled indicates thatthe khaththath has a clear identity in terms of heredity that continues from teacherto teacher. The method used in this study is a qualitative method, the data obtainedfrom observations, interviews and documentation. So that researchers will examinehow the process and stages of learning khat. and the author will examine the hadithat-Tirmidhī number 3638 contained in the khat certificate, and the backgroundof thoughts and views on the hadith at-Tirmidhī number 3638. Of course, he willexamine the parts of the khat diploma and the influence of the hadith at-Tirmidhīnumber 3638 on beauty preaching khaththath.